Hazardous impact of diclofenac exposure on thè behavior and antioxidant defense System in Nauphoeta cinerea (2020)
Environmental pollution by pharmaceuticals such as diclofenac (DCF) is globally acknowledged to be a threat to thè ecosystems. Nauphoeta cinerea is an important insect with valuable ecological role. The present investigation aimed to elucidate thè impact of DCF on insects by assessing thè behavior and antioxidant defense response in nymphs ofN. cinerea exposed to DCF-contaminated food at 0,0.5,1.0 and 2.0 pg kg~* feed for 42 successive days. Subsequent to exposure period, neurobehavioral analysis using video-tracking software in a novel apparatus was performed before estimation of biochemical endpoints in thè head, midgut and hemolymph of thè insects. Results indicated that DCF-exposed insects exhibited marked reduction in thè maximum speed, total distance traveled, mobile episodes, total mobile time, body rotation, absolute turn angle and path efficiency, whereas thè total freezing time was increased compared with thè control. The diminution in thè exploratory activities of DCF-exposed insects was substantiated by heat maps and track plots. Additionally, DCF elicited marked diminution in antioxidant enzyme and acetylcholinesterase (AChE) activities along with increase in nitric oxide (NO), reactive oxygen and nitrogen species (RONS), and lipid peroxidation (LPO) levels in thè head, midgut and hemolymph of thè insects. Taken together, DCF elicited neurotoxicity and oxido-inflammatory stress in exposed insects. N. cinerea may be a suitable model insect for environmental risk assessment of pharmaceuticals in non-target insect species.